Implementation of Teaching Game for Understanding Approach for Improvement Man To Man Marking (Defense) to Beginner Basketball Player - Atri Widowati; Grafitte Decheline; Yusra Dinafi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Teaching Games for Understanding is basically learning by the game level that suitabled with the development and activity of modification game learning that is centered on tactical problems and the student must be to solve it. Physical Education learning approaches to introduce the meaning of playing in sport to students. The purpose from this research is to improve known player basketball about Man to Man Marking in playing basketball used teaching games for understanding tactical approach. This research is qualitative research, observative descriptive design to know implementation of new learning methods in Physical education to students, or athletes by using teaching games for understanding. In this research had been done by observation, using triangulation data, given practice Teaching games for understanding methods, improving known was by questionnaire and skill results after giving teaching games for understanding method and documentation from the activities. This approach was an activity to make it easy for the students to deliver material, especially about the tactic games in sport. Furthermore, this approach is a part from Tactical Approach, where students or athletes will do some game modification that is almost the same with the real game. Technique from the game will be the same, but sometimes the field, rule of game, and player who can play will be modified by the teacher. The focus from students was in the tactical game. So, they must understand their position and their assignment in the field during the game. From the research, answered from students and their opinion about the Teaching Games for understanding tactical approach for better known man to man marking defense, the conclusion that 66,7% from total sample have good known about the teaching games for understanding, but 33,3% from others, have good known yet about the tactical approach. That is, the teaching games for understanding for students and athletes must be more socialized, especially in Jambi.